(untitled) (Journal of Pharmaceutical Negative Results, 2020)
Background: Lumbar canal stenosis is a debilitating condition that results from the narrowing of the spinal canal, and the management of this condition especially at advanced stages involve surgical treatment once conservative methods have been tried and proved to be ineffectual. Objectives: Compare results with the use of only classic laminectomy with the use of laminectomy and fixation in LCS patients. Study design : A prospective study Place and duration of study. Department of orthopedic unit MMC hospital mardan from 05-july 2019 to 05 dec 2019 Methods This prospective study consisted of 100 LCS patients, switched by randomisation into two groups: Group A who underwent the classic laminectomy and Group B who, in addition to classic laminectomy, received the stabilization. Patients’ pain levels (measured with the visual analog scale) preoperatively and at the time of latest follow-up as well as the Disability Index (ODI) were collected, in addition to the number of complications and length of hospital stay. Results There was less pain in patients of Group B as 85% show better improvement in pain relief as compared to 70% of Group A Though functional improvement also favours group B with Average improvement of ODI score of 40 % as compared to 25% in Group A. However complications rate found higher in Group B patients as 4 out of 20 patients (20%) developed some complications as against to 2 out of 20 in Parker reported that Group B had common complications observed in other studies they underwent infections and hardware failure. Conclusion Posterior lumbar interbody fusion L5-S1 significantly improves improvement or back pain and overall functioning in comparison to laminectomy alone, but with more times the incidence of complications and two extra days in the hospital. There is much to be learnt about who should be given such treatment as patient selection is paramount. Keywords: Spine surgery, lumbar canal stenosis, laminectomy, affect fixation, results.